Estudio de las nuevas tendencias del turismo post covid-19 en los principales mercados turísticos internos de Tungurahua. - Palma Andagua, Katherine Michell (2025)
This research takes place in the province of Tungurahua and aims to analyze the main post-COVID-19 tourism trends. This has been achieved through the identification of local businesses and the exploration of traveler behavior following the health crisis. To accomplish this, a mixed methodology was applied, combining both qualitative and quantitative approaches. A total of 385 surveys were conducted with tourists, who provided information about their main motivations and trends. These were collected through a questionnaire. In addition, a semi-structured questionnaire was used in interviews with the owners or main representatives of tourism establishments who agreed to collaborate with the development of this document. The collected data were processed using analytical–synthetic, and inductive–deductive methods to ensure a comprehensive approach to the information concerning tourism supply and demand. The main findings reveal that the province of Tungurahua is a highly recommended destination that attracts tourists with a high spending capacity. However, the tourism services offered are largely focused on Baños de Agua Santa throughout the year, followed by seasonal activities in Ambato and Pillaro. Therefore, strategies are being developed to diversify the tourism offer across the entire province and for various tourist segments in all cantons.